A Fluorous Proline Organocatalyst with Acetone‐Dependent Aldolase Behavior. Issue 28 (30th August 2013) - Miranda, Pedro O.; Llanes, Patricia; Torkian, Laleh; Pericàs, Miquel A.
Abstract: A polyfluoroalkyl derivative of 4‐hydroxyproline, assembled through a 1, 2, 3‐triazole linker (i.e., 7 ), displays high catalytic activity and enantioselectivity in aldol reactions of acetone with aromatic aldehydes featuring electron‐withdrawing groups. The scope of the reaction with respect to the aldehyde acceptor can be expanded with the use of a bifunctional urea cocatalyst. The presence of the fluorous tag allows the aldol reactions to be performed in a perfluorohexane/acetone biphasic system. In this way, both the catalyst and the perfluorinated solvent can be easily recycled and reused (>6 times). In addition, the combination of the fluorous tag, triazole linker, and catalytic proline unit confers unprecedented substrate specificity for acetone upon7 . Abstract : An unusual specificity for acetone as the nucleophile is observed in asymmetric cross‐aldol reactions with aldehydes catalyzed by a fluorous proline derivative. The reactions take place in acetone/perfluorohexane under biphasic conditions, and the valuable catalyst/perfluorohexane phase can be repeatedly recycled.